A background correction algorithm for Van Allen Probes MagEIS electron flux measurements. Issue 7 (14th July 2015) - Claudepierre, S. G.; O'Brien, T. P.; Blake, J. B.; Fennell, J. F.; Roeder, J. L.; Clemmons, J. H.; Looper, M. D.; Mazur, J. E.; Mulligan, T. M.; Spence, H. E.; Reeves, G. D.; Friedel, R. H. W.; et al.
Abstract: We describe an automated computer algorithm designed to remove background contamination from the Van Allen Probes Magnetic Electron Ion Spectrometer (MagEIS) electron flux measurements. We provide a detailed description of the algorithm with illustrative examples from on‐orbit data. We find two primary sources of background contamination in the MagEIS electron data: inner zone protons and bremsstrahlung X‐rays generated by energetic electrons interacting with the spacecraft material. Bremsstrahlung X‐rays primarily produce contamination in the lower energy MagEIS electron channels (∼30–500 keV) and in regions of geospace where multi‐MeV electrons are present. Inner zone protons produce contamination in all MagEIS energy channels at roughly L < 2.5. The background‐corrected MagEIS electron data produce a more accurate measurement of the electron radiation belts, as most earlier measurements suffer from unquantifiable and uncorrectable contamination in this harsh region of the near‐Earth space environment. These background‐corrected data will also be useful for spacecraft engineering purposes, providing ground truth for the near‐Earth electron environment and informing the next generation of spacecraft design models (e.g., AE9). Key Points: MagEIS instrument can quantify and remove background contamination from electron measurements Most earlier measurements suffer from unquantifiable and uncorrectable contamination Two primary sources of contamination are found: inner zone protons and bremsstrahlung X‐rays generated by energetic electrons